The Practices, Perceptions, and Beliefs of Traditional Birth Attendants Regarding Early Breastfeeding Initiation in Zimbabwe: A Qualitative Study - Gladys Mugadza (Mashhad University of Medical Sciences, 2018)
Background & aim: Early breastfeeding initiation (EBFI) defined as giving breast milk within the first hours following birth, which is recommended as a simple strategy for the enhancement of neonatal health and survival. This descriptive qualitative study was conducted to explore the practices, perceptions and beliefs of renowned traditional birth attendants (TBA) regarding EBFI in Chipinge rural community, Zimbabwe. Methods: The study population was selected through purposive sampling technique. One-on-one interview was conducted for the purpose of unearthing sensitive issues regarding EBFI. The data were collected using an unstructured in-depth interview to explore the practices, perceptions, and beliefs regarding EBFI. Data analysis was carried out using thematic analysis. To this end, the data were presented in thematic categories using the deductive approach and coded into subthemes, which were then merged into themes. The trustworthiness of the study was enhanced through credibility, dependability, confirmability and transferability. Results: The emerged themes included EBFI preparation, EBFI and significance of colostrum, and determinants of EBFI. The findings revealed that EBFI was not only related to physical and emotional interactions, but also associated with a totality of the person, involving sociocultural ties. The EBFI is viewed as a predictor of maternal sociocultural integrity and the legitimacy of the newborn. In the context under study, failure to breastfeed or to initiate breastfeeding early is thought to be a result of the mother's past immorality. Breastfeeding in Chipinge community goes beyond the mother-baby interaction. Conclusion: It encompasses the whole person,  that is the physical, social, cultural and spiritual ties. Under this condition, the mother should testify and undergo a ritual cleansing to rectify the problem.